Delegation and communication - Malin Arve; Takakazu Honryo (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
This paper analyzes delegation and joint decision making in an environment with private information and partially aligned preferences. We compare the benefits of these two decision making procedures as well as the interaction between them. We give a condition under which delegation is preferred to ex post joint decision making and we show how the interaction between delegation and ex post joint decision making always crowds out delegation. Finally, we analyze how the availability of the principal at the communication stage affects our results.
Keywords: D23; D82; L23; 330